2022
DOI: 10.7759/cureus.27337
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mesenchymal Stem Cells in the Treatment of Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) is a chronic disease characterized by inadequate or absent insulin production due to the autoimmune destruction of beta (β) cells in the pancreas. It was once called "juvenile diabetes" since the disease frequently occurs in children, but it can also develop in adults. According to the International Diabetes Federation, an estimated 700 million adults will suffer from diabetes by 2045. Although the exact cause of diabetes remains unknown, it is hypothesized that genetic factors, environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Research has demonstrated the capacity of MSC to change into different categories of skin cells, clusters of islet-like cells, and renal epithelial cells ( Brasile et al ., 2019 ; Jo et al ., 2021 ; Jayasinghe et al ., 2022 ). These three studies are merely a few illustrations of the substantial amount of information that has been gathered in the past ten years, which supports the potency of MSC to transdifferentiate when transplanted in vivo.…”
Section: Search Resultsmentioning
confidence: 99%
“…Research has demonstrated the capacity of MSC to change into different categories of skin cells, clusters of islet-like cells, and renal epithelial cells ( Brasile et al ., 2019 ; Jo et al ., 2021 ; Jayasinghe et al ., 2022 ). These three studies are merely a few illustrations of the substantial amount of information that has been gathered in the past ten years, which supports the potency of MSC to transdifferentiate when transplanted in vivo.…”
Section: Search Resultsmentioning
confidence: 99%
“…MSCs can generate many bioactive factors, such as TGF-α, HGF, IDO, PGE 2 , which play important roles in modulating immuno-cell functions, such as inhibiting T cell proliferation, dendritic cell activation, and inflammatory cytokine generation ( Soleymaninejadian et al, 2012 ; Jiang and Xu, 2020 ). On the basis of generation immunomodulating factors, MSCs inhibit the onset of type 1 diabetes and reverse β-cell functions ( Vija et al, 2009 ; Jayasinghe et al, 2022 ). However, type 2 diabetes is different from type 1 diabetes, and immunomodulating functions may not be the reason for MSCs repairing damaged β-cells in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain adequate blood glucose levels, T1D patients need exogenous insulin administration in the form of subcutaneous injections. Alternative treatments include islet cell transplantation or whole pancreas transplantation, which requires subsequent immunosuppressive therapy [ 48 , 49 , 50 , 51 , 52 , 53 ]. Up to 80% of the transplanted islets are lost before becoming integrated into tissue due to acute inflammatory responses and release of the pro-inflammatory cytokines IL-1β, TNFα, and IFNγ [ 9 , 48 , 54 , 55 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative treatments include islet cell transplantation or whole pancreas transplantation, which requires subsequent immunosuppressive therapy [ 48 , 49 , 50 , 51 , 52 , 53 ]. Up to 80% of the transplanted islets are lost before becoming integrated into tissue due to acute inflammatory responses and release of the pro-inflammatory cytokines IL-1β, TNFα, and IFNγ [ 9 , 48 , 54 , 55 , 56 , 57 ]. The success of islet transplantation is also challenged by allo-immune graft rejection and recurrence of autoimmunity [ 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation